Clinical utility of paced finger tapping assessment in idiopathic normal pressure hydrocephalus - Shimizu, Yoko; Tanikawa, Motoki; Horiba, Mitsuya; Sahashi, Kento; Kawashima, Shoji; Kandori, Akihiko; Yamanaka, Tomoyasu; Nishikawa, Yusuke; Matsukawa, Noriyuki; Ueki, Yoshino; Mase, Mitsuhito (Frontiers in Human Neuroscience, 2023)
Abstract Background The Finger Tapping (F-T) test is useful for assessing motor function of the upper limbs in patients with idiopathic normal pressure hydrocephalus (iNPH). However, quantitative evaluation of F-T for iNPH has not yet been established. The purpose of this study was to investigate the usefulness of the quantitative F-T test and optimal measurement conditions as a motor evaluation and screening test for iNPH. Methods Sixteen age-matched healthy controls (mean age 73±5years;7/16 male) and fifteen participants with a diagnosis of definitive iNPH (mean age 76±5years; 8/15 male) completed the study (mean ± standard deviation). F-T performance of the index finger and thumb was quantified using a magnetic sensing device. The performance of repetitive F-T by participants was recorded in both not timing-regulated and timing-regulated conditions. The mean value of the maximum amplitude of F-T was defined as M-Amplitude, and the mean value of the maximum velocity of closure of F-T was defined as cl-Velocity. Result F-T in the iNPH group, with or without timing control, showed a decrease in M-Amplitude and cl-Velocity compared to the control group. We found the only paced F-T with 2.0Hz auditory stimuli was found to improve both M-Amplitude and cl-Velocity after shunt surgery. 3 Conclusions The quantitative assessment of F-T with auditory stimuli at the rate of 2.0 Hz may be a useful and potentially supplemental screening method for motor assessment in patients with iNPH.